2014
DOI: 10.4172/2090-2778.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Management of Neonatal Malaria: A Review

Abstract: The burden of neonatal malaria was thought rare in the past because of presence of protective factors such as maternal antimalarial antibodies, lactoferrin, secretary IgA in human milk and HbF. In endemic areas for malaria, this group (neonates) needs to be more focused for such infection, as due to difficulty in diagnosis it may be representing only the tip of iceberg. In addition there is little information on the use of artimisinin-based combination therapy in neonates. This review aims to discuss all these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…It was believed that the fetal hemoglobin provided some protection to the newborn against malaria [19]. This, however, is not the case as studies across Africa including Nigeria have shown neonatal malaria rates ranging from 0 to 54.2% [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that the fetal hemoglobin provided some protection to the newborn against malaria [19]. This, however, is not the case as studies across Africa including Nigeria have shown neonatal malaria rates ranging from 0 to 54.2% [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%